Sustainable Energy Transition for Renewable and Low Carbon Grid Electricity Generation and Supply - Kabeyi, Moses Jeremiah Barasa; Olanrewaju, Oludolapo Akanni (Frontiers in Energy Research, 2022)
The purpose of this study is to review the role of energy in sustainable development by ensuring sustainability in electricity generation, supply, and consumption. Global electricity generation remains dominated by fossil fuels with renewable energy sources contributing a smaller proportion. Sustainable development needs sustainable energy which should be reliable, stable, good quality, affordable non-polluting and socially acceptable. Whereas sustainable development has social, economic, and environmental pillars, sustainability of energy and electricity generation systems are assessed by a five-dimensional approach consisting of environmental, economic, social, technical, and institutional sustainability as a strong measure of resource and system sustainability. New technology should be developed and exploited for to maximize use of abundant but intermittent renewable sources a sustainable mix with limited nonrenewable sources optimized to minimize cost and environmental impact but maintained quality, stability, and flexibility of an electricity supply system. This review recommends the use of the three main strategies to minimize carbon emissions in the energy transition. These are conventional mitigation, negative emissions technologies which capture and sequester carbon emissions and finally technologies which alter the global atmospheric radiative energy budget to stabilize and reduce global average temperature. Besides low emissions, a sustainable electricity grid system should be stable and supply reliable, affordable, and socially acceptable electricity. A sustainable electricity system needs facilitating technology, policy, strategies and infrastructure like smart grids, and models.